Cara Pembuatan Tahu Di Pabrik Tahu Desa Lubuk Sahung Kecamatan Sukaraja Kabupaten Seluma Provinsi Bengkulu - Yuliansyah, Yuliansyah; Sari, Yosita Tri Purnama; Tentara, Brend; Putri, Wulandari Indah Andi; Sumartono, Eko (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Tofu is one of the popular soybean processed products in Indonesia because of its high nutritional content and affordable price. This study aims to describe the process of making tofu in one of the home tofu factories in Lubuk Sahung Village, Sukaraja District, Seluma Regency, Bengkulu Province. The methods used are direct observation, interviews, and documentation of the tofu production process. The results of the study indicate that the tofu making process is carried out through several main stages, namely: soaking, grinding, boiling, filtering, sedimentation, molding, and cutting. The process is carried out semi-manually using simple equipment but still paying attention to food sanitation standards. This activity has a significant economic impact on the surrounding community.